Core–shell structured hierarchically porous NiO microspheres with enhanced electrocatalytic activity for oxygen evolution reaction. Issue 5 (11th April 2018) - Ma, Yali; Wang, Xue; Sun, Xiaodong; Gao, Tunan; Liu, Yunling; Zhang, Ling; Huo, Qisheng; Qiao, Zhen-An
Abstract : We present a one-pot synthetic strategy to synthesize hierarchically porous NiO microspheres with enhanced activity for OER. Abstract : The design and synthesis of efficient catalysts to substitute the currently effective and sturdy electrocatalysts composed of precious metal-based materials ( e.g., IrO2 and RuO2 ) for the oxygen evolution reaction (OER) is still a huge challenge. In this regard, nickel-based OER catalysts with specific properties have drawn widespread attention. Herein, we prepared core–shell structured hierarchically mesoporous NiO microspheres through the thermal decomposition of Ni(OH)2 microspheres, which were synthesized through a one-pot hydrothermal method. The obtained NiO microspheres possess numerous mesopores, a high BET surface area, and 2D nanosheet-like shells, which largely promote mass/charge transportation and reduce ion transport pathways. By increasing the molar ratio of HMTA/Ni 2+, the thickness of the outer nanosheet-like shell can be varied in the range of 0–35 nm. In particular, the NiO-300/ r = 2 microspheres possess excellent properties for OER (overpotential of 360 mV to reach 10 mV cm −2 ), compared with previously-reported Ni-based materials. Furthermore, improved activity with an overpotential of 340 mV was reached by introducing Co.